2018
DOI: 10.1542/peds.2018-1016
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Age, Health, and Educational Outcomes in Adolescents

Abstract: BACKGROUND AND OBJECTIVES: As outcomes for extremely premature infants improve, up-todate, large-scale studies are needed to provide accurate, contemporary information for clinicians, families, and policy makers. We used nationwide New Zealand data to explore the impact of gestational age on health and educational outcomes through to adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…Active labor occurred most commonly after 6 cm of dilation, and cervical dilation progressed more slowly than previously thought, especially between 4 and 6 cm. These results represent a departure from the Friedman curve and now inform our clinical knowledge of median labor progression in modern obstetric practice [6] . Additionally, inherent differences in the progress of labor have been attributed to specific patient characteristics or clinical conditions.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Active labor occurred most commonly after 6 cm of dilation, and cervical dilation progressed more slowly than previously thought, especially between 4 and 6 cm. These results represent a departure from the Friedman curve and now inform our clinical knowledge of median labor progression in modern obstetric practice [6] . Additionally, inherent differences in the progress of labor have been attributed to specific patient characteristics or clinical conditions.…”
Section: Introductionsupporting
confidence: 53%
“…Additionally, inherent differences in the progress of labor have been attributed to specific patient characteristics or clinical conditions. Maternal obesity, gestational age beyond 37 weeks and even fetal sex have been shown to influence labor progression [6] . In our study, we examined a contemporary labor database to identify labor curves and predictors of vaginal delivery in pregnant women undergoing medically indicated preterm IOL.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated a higher frequency of short and long term morbidity in early-term infants [ 3 , 4 , 5 ]. Neurodevelopmental outcomes of those infants are now being closely studied and initial reports focusing on cognition, school performance and behavioral problems demonstrate delays and deviations of the early-term infants as compared to the full-term infants [ 7 , 8 , 9 , 11 , 13 , 14 , 15 , 17 ]. Epilepsy and sensorineural defects have also been shown to be related to early-term deliveries [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to perinatal outcomes, infants born in the early-term period are considered to be at risk for adverse long-term outcomes in several aspects, especially in neurodevelopment [ 3 , 5 ]. It has been reported that compared with children born full-term, early-term birth has a negative impact on cognitive [ 6 , 7 ] and motor development [ 8 , 9 ], behavior and emotional status [ 8 , 10 , 11 ], communication skills and social outcomes [ 8 , 12 ], school performance and academic achievements [ 8 , 13 , 14 , 15 ]. However, there are large variations among published studies, including methodological diversity and heterogeneity of data [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Late preterm infants (34 +0 -36 +6 weeks' gestation) comprise the majority of preterm births, 1 2 and are physiologically and metabolically immature, 3 with a higher risk of morbidity and mortality in the neonatal period than term infants. 4 Late preterm infants are more likely to be diagnosed with cerebral palsy, 5 6 developmental delay [7][8][9] and cognitive impairment [9][10][11][12][13] compared with term infants. Late preterm infants also experience frequent episodes of intermittent hypoxaemia (IH) 14 ; transient repetitive decreases in oxygen saturation not associated with apnoea but potentially causing similar organ hypoxia.…”
Section: Introductionmentioning
confidence: 99%